Electrophysiological correlates of emotional face processing after mild traumatic brain injury in preschool children. - D'Hondt, Fabien; Lassonde, Maryse; Thebault-Dagher, Fanny; Bernier, Annie; Gravel, Jocelyn; Vannasing, Phetsamone; Beauchamp, Miriam (Cognitive, Affective & Behavioral Neuroscience, 2017)
Evidence suggests that social skills are affected by childhood mild traumatic brain injury (mTBI), but the neural and affective substrates of these difficulties are still underexplored. In particular, nothing is known about consequences on the perception of emotional facial expressions, despite its critical role in social interactions and the importance of the preschool period in the development of this ability. This study thus aimed to investigate the electrophysiological correlates of emotional facial expressions processing after early mTBI. To this end, 18 preschool children (mean age 53 ± 8 months) who sustained mTBI and 15 matched healthy controls (mean age 55 ± 11 months) were presented with pictures of faces expressing anger, happiness, or no emotion (neutral) while event-related potentials (ERP) were recorded. The main results revealed that P1 amplitude was higher for happy faces than for angry faces, and that N170 latency was shorter for emotional faces than for neutral faces in the control group only. These findings suggest that preschool children who sustain mTBI do not present the early emotional effects that are observed in healthy preschool children at visuospatial and visual expertise stages. This study provides new evidence regarding the consequences of childhood mTBI on socioemotional processing, by showing alterations of emotional facial expressions processing, an ability known to underlie social competence and appropriate social interactions.